2009
DOI: 10.1017/s1092852900020204
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Analysis of the Safety and Tolerability of Desvenlafaxine Compared with Placebo in the Treatment of Major Depressive Disorder

Abstract: Introduction: The safety and tolerability profiles of antidepressants can often influence the treatment choices of clinicians treating major depressive disorder. The purpose of this investigation was to characterize the safety and tolerability of desvenlafaxine (administered as desvenlafaxine succinate) in treating depression.Methods: An integrated analysis of all short-term, randomized, double-blind, placebo-controlled registration studies for major depressive disorder (four flexible-dose and five fixed-dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
48
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 20 publications
8
48
1
1
Order By: Relevance
“…Studies investigating desvenlafaxine at lower doses (ie, 50 and 100 mg/d) have demonstrated better tolerability and lower occurrences of AEs [14,15,20].…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating desvenlafaxine at lower doses (ie, 50 and 100 mg/d) have demonstrated better tolerability and lower occurrences of AEs [14,15,20].…”
Section: Discussionmentioning
confidence: 99%
“…In an early study of 132 patients with depressive disorders, loss of sexual interest (characterized by loss of libido or decrease of sexual desire or potency) was reported by 72% of patients with unipolar disorder and 77% of those with bipolar disorder [15]. Loss of sexual desire may be the presenting complaint in some patients who are found to have significant depressive symptoms only after direct questioning.…”
Section: Sexual Dysfunction In Depressionmentioning
confidence: 99%
“…143 A strong dose-response effect on tolerability was reported, but both 50 mg and 100 mg doses were well tolerated. 144,177 Discontinuation rates due to adverse events were similar to those with placebo. The most common adverse event was transient mild to moderate nausea.…”
mentioning
confidence: 61%
“…108 [134][135][136]140 Higher remission rates of bupropion (46%) vs venlafaxine (33%) and similar responder rates (HAM-D e , MADRS c ) after 6-8 weeks treatment. 143,144 Bupropion may be suitable to augment citalopram and in major depressions. 146,150 Bupropion IR: tremor (22%), menstrual complaints (5%), hypertension and impaired sleep (4%).…”
Section: Escitaloprammentioning
confidence: 99%
See 1 more Smart Citation